Aceh Pasca Pilkada 2017: Dari Populisme hingga Harapan Demokrasi Baru - Teuku Kemal Fasya (Tashwirul Afkar, 2024)
This article analyzes the opportunities political change in Aceh post-local election 2017, which can be called a new phase towards the post-conflict democracy and tsunami transition. Simultaneous local election in 2017, either in provincial or districts/municipals in Aceh, are marked with massive defeat of Aceh Party (PA) in most areas. This reality shows that there is a decline of support from the ex-combatant’s political forces in government politics. This article also sees the opportunity of the Irwandi Jusuf - Nova Iriansyah (IrNo), as the winner of governor election to be a new political hope in Aceh, replacing the political power that is attached to identity politics with the spirit of ethnonationalism, into a new local substantial democracy. However, this new government will also face the challenge of political involution which is the trap of populism; something that has been implicated in the government elected through a democratic process. One of the agenda of populism that could threaten substantial democracy is to harden the politics of Islamic discriminatory law against minority groups.